2012
DOI: 10.1007/bf03341746
|View full text |Cite
|
Sign up to set email alerts
|

Student Feedback on OSPE: An Experience of a New Medical School in Saudi Arabia

Abstract: Objective Structured Practical Examination (OSPE) is widely used in the assessment for medical students' practical skills. OSPE was introduced to the Faculty of Medicine of King Fahad Medical City in September 2008. The aim of this study is to investigate the medical students' feedback on OSPE. Third year female medical students (n=38) enrolled in Respiratory, Gastrointestinal, Urogenital systems blocks were included. A questionnaire was distributed to assess students' evaluation of the OSPE. Grades of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…Rehman stated that OSPE is better and unbiased system of examination as it is neither stressful nor dependent on mood of the examiner and there is no fear of facing the examiner (Rehman et al, 2012). In corroboration with us there are studies that have reported that OSPE is fairer, more transparent and objective in comparison to Traditional Practical Examination and thus effective and useful assessment tool (Al-Mously, 2012;Rao et al, 2018). Our findings are in agreement with Harden and Gleeson who recommended that OSCE should be combined with traditional long case (Harden and Gleeson, 1979).…”
Section: Discussionsupporting
confidence: 72%
“…Rehman stated that OSPE is better and unbiased system of examination as it is neither stressful nor dependent on mood of the examiner and there is no fear of facing the examiner (Rehman et al, 2012). In corroboration with us there are studies that have reported that OSPE is fairer, more transparent and objective in comparison to Traditional Practical Examination and thus effective and useful assessment tool (Al-Mously, 2012;Rao et al, 2018). Our findings are in agreement with Harden and Gleeson who recommended that OSCE should be combined with traditional long case (Harden and Gleeson, 1979).…”
Section: Discussionsupporting
confidence: 72%
“…Students' feedback is considered a key indicator for successful implementation of VOSPE. Based on the students' feedback response 64%was stress freer in absence of examiner when comparing with 63.2% felt stressed in the presence of examiner in OSPE [11]. In absence of examiner the 73% of student agree that the information was very clear and does not miss the examiner during the performance, but only 5% of student who miss the examiner, focused towards expecting clues to get the answer in practical performance while the remaining 22% of student was neutral.…”
Section: Discussionmentioning
confidence: 97%
“…From the reviewed studies, only OSCE's used new practical methods and progressed using video recording, computer assisted procedures and video projectors. Although studies shown that OSPE was a reliable method, the current OSPE procedures carried with single or two OSPE stations is not enough to test the learning outcome of the student [11]. So an idea emerged to introduce videotape OSPE in the ROSPE, to evaluate the students' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have raised the same concern that time is a problem with OSPE and have stressed that it should not become an exercise how fast students can perform a technique but rather focus on how well they can perform. [ 12 15 ] Even though students felt intimidated by the OSPE examination, they were enthusiastic because of its objectivity, uniformity and reliability. The participants found OSCE to be less stressful than the conventional examination, and this allowed them to perform better.…”
Section: Discussionmentioning
confidence: 99%